2017
DOI: 10.1007/s10021-017-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Effects on Biomass Versus Top-Down Effects on Identity: A Multiple-Lake Fish Community Manipulation Experiment

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the KNAW public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-making activity or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…Furthermore, fish biomass in lakes is primarily driven by bottom-up effects (e.g. Hanson & Leggett, 1982; Lemmens et al , 2018; Matsuzaki et al , 2018) – a finding also revealed in our study at the aggregate biomass level, which did not differ among lake types despite radically different fish community composition. As species richness was substantially lower in unmanaged lakes, the lake type-specific small-bodied non-game species that colonized unmanaged lakes can reach higher biomasses and abundances in these lakes types compared to managed lakes.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, fish biomass in lakes is primarily driven by bottom-up effects (e.g. Hanson & Leggett, 1982; Lemmens et al , 2018; Matsuzaki et al , 2018) – a finding also revealed in our study at the aggregate biomass level, which did not differ among lake types despite radically different fish community composition. As species richness was substantially lower in unmanaged lakes, the lake type-specific small-bodied non-game species that colonized unmanaged lakes can reach higher biomasses and abundances in these lakes types compared to managed lakes.…”
Section: Discussionsupporting
confidence: 83%
“…cladocerans such as Bosmina longirostris, Dunhevedia, and cyclopoid copepods) of fish. This is in line with earlier investigations on the impact of predation by fish on zooplankton (Lemmens, Declerck, Tuytens, Vanderstukken, & De Meester, 2018;Mamani, Koncurat, & Boveri, 2019).…”
Section: Effects Of Lhc On the Taxonomic And Trait Community Compossupporting
confidence: 93%
“…Submerged plant communities play a central role in the ecological condition and sustainability of freshwater systems, and changes in the abundance and composition of such communities may have significant effects, not least on water quality. In shallow lakes, submerged plants play a key role in suppressing phytoplankton growth (Lemmens et al, 2018) and improving and maintaining water clarity. Any impact of common carp activities is thus likely to be ecologically significant.…”
Section: Introductionmentioning
confidence: 99%